Preliminary Study of Spatial Verification for Wind Model Output Against Oceansat-2 Satellite - Mujiasih, Subekti; Prasetyo, Eko (IPTEK The Journal for Technology and Science, 2025)
Information on wind, which is one of selected marine weather forecasts, is very important to support sea transportation safety. To increase the forecast quality, the parameter should be verified. This study will provide spatial verification wind from wind waves model output against wind from oceansat-2 Satellite data and AWS on board (Automatic Weather Station). Wind of model output includes hindcast and forecast 18 hours ahead. The chosen sample data were some extreme conditions in Java Sea during November 2012 until October 2013. Despite the same trend of wind direction displayed by both model output and Oceansat-2, the study result found significant gap of wind speed. This information will be recommendation for marine weather forecaster.